Future Trends in Angler Behavior Based on a Delphi Study in the Nordic Countries - van den Heuvel, Lotte; Aas, Øystein; Agnarsson, Sveinn; Björkvik, Emma; Blicharska, Malgorzata; Blyth, Samuel; Gundelund, Casper; Husa, Miikka; Olaussen, Jon Olaf; Pellikka, Jani; Rönnbäck, Patrik; Stensland, Stian; et al. (Wiley-Blackwell, 2024)
Recreational fisheries are dynamic social-ecological systems. Identification of anticipated future trends supports the design of policies and management to deliver outcomes for fisheries resources, users, and communities. To this end, we applied a forecasting method (i.e., Delphi survey) to recreational fisheries in five Nordic countries. The survey consisted of three rounds and included 20 diverse experts from each country. The study focused on expert perceptions of future trends in angler behaviors linked to specific angling activities (e.g., gear used, species targeted), and more general behavior (e.g., social media use, stewardship). Experts unanimously expected increases in fly fishing, stewardship, and use of angling-related technologies and social media platforms in the upcoming decade. Results can guide future research, management, and collaboration related to recreational fishing in the Nordic countries and beyond.
Keywords: fishing; recreational fishing; Nordic cooperation; Nordic identity; leisure activities